CIVIL SOCIETY; UPAYA MENCIPTAKAN MASYARAKAT MADANI - Yunus, Nur Rohim (JURNAL ILMU SYARIAH, 2013)
Civil society is a significant element in building democracy. One essential condition for democracy is the creation of public participation in decision-making processes carried out by the state or government. Civil society requires civic engagement, namely the involvement of citizens in social associations. Civic engagement allows the growth of openness, trust and tolerance among one another.